An arabinogalactan isolated from Pollen Typhae induces the apoptosis of RKO cells by promoting macrophage polarization. (1st January 2023) - Xu, Yongbin; Wang, Qun; Chen, Jie; Wu, Jianjun; Su, Juan; Gao, Wei; Chen, Weihao; Shi, Songshan; Wang, Shunchun; Wang, Huijun
Abstract: An arabinogalactan (PTPS-1-2) was isolated and characterized from Pollen Typhae, and its potential antitumor effects on activating macrophages to produce immunomodulatory factors and promoting apoptosis in colorectal cancer cells were investigated. Structural characterization showed that PTPS-1-2 had a molecular weight of 59 kDa and was composed of rhamnose, arabinose, glucuronic acid, galactose, and galacturonic acid with a molar ratio of 7.6: 17.1: 6.5: 61.4: 7.4. Its backbone was predominantly composed of T-β-D-Gal p, 1, 3-β-D-Gal p, 1, 6-β-D-Gal p, 1, 3, 6-β-D-Gal p, 1, 4-α-D-Gal p A, 1, 2-α-L-Rha p, additionally, branches contained 1, 5-α-L-Ara f, T-α-L-Ara f, T-β-D-4-OMe-Glc p A, T-β-D-Glc p A and T-α-L-Rha p . PTPS-1-2 activated RAW264.7 cell by triggering the NF-kB signaling pathway and M1 macrophage polarization. Furthermore, the conditioned medium (CM) of Mφ pretreated with PTPS-1-2 exerted marked antitumor effects by inhibiting RKO cell proliferation and suppressing cell colony formation. Collectively, our findings suggested that PTPS-1-2 might be a therapeutic option for the prevention and treatment of tumors. Graphical abstract: Unlabelled Image